Development of Candidate Antigens for Rapid Test Kit to Detect Autoantibodies in Patients with Systemic Lupus Erythematosus - Wisnu Barlianto; Hani Susianti; Singgih Wahono; Nelly Ismayasih; Rossy Meilani; Kusworini Handono (Research Journal of Life Science, 2017)
Systemic Lupus Erythematosus (LES) is an autoimmune inflammatory disease characterized by the formation of anti-nuclear antibodies (ANA) and anti-double stranded DNA (anti-dsDNA) antibodies as diagnostic markers. Detection of such autoantibodies requires advanced equipment and trained personnel.This study was conducted to acquire candidate antigens that can be used for rapid test kit for practical and accurate detection of ANA and anti-dsDNA to speed up SLE diagnosis.Nuclear proteins and DNA derived from cell lines, hair follicles, and leukocytes of SLE patients and healthy individuals were isolated using QiaGEN kit and modified-manual procedure. Antigen-antibody bonds were tested by dot blot assay.The strongest binding between DNA antigens of a healthy individual and antibodies occurred at dilution factors of 1:5,120 for the antigen and 1:2,560 for the antibody. The strongest binding between nuclear protein antigens from the cell line and antibodies occurred at dilution factors of 1:512 for the antigen and 1:1,600 for the antibody.Nuclear antigens derived from cell line and DNA antigens of healthy individuals were antigen candidates for the development of ANA and anti-dsDNA rapid detection tests.